Berkshire beyond Buffett : the enduring value of values - Cunningham, Lawrence A., 1962- (Columbia Business School publishing., 2014)
Berkshire Hathaway, the 300 billion conglomerate that Warren Buffett built, is among the world's largest and most famous corporations. Yet, for all its power and celebrity, few people understand Berkshire, and many assume it cannot survive without Buffett. This book proves that assumption wrong. In a comprehensive portrait of the distinct corporate culture that unites and sustains Berkshire's fifty direct subsidiaries, Lawrence A. Cunningham unearths the traits that assure the conglomerate's perpetual prosperity. Riveting stories recount each subsidiary's origins, triumphs, and journey to Be.